A new species of Phalangogonia Burmeister (Coleoptera: Scarabaeidae: Rutelinae: Anoplognathini) from Costa Rica - Smith, Andrew B.t. (Zootaxa, 2003)
Phalangogonia hawksi sp. n. from the Osa Peninsula of Costa Rica is described. The genus Phalangogonia Burmeister now includes nine species. An updated key to the species in this genus is provided to accommodate the new species.